2018
DOI: 10.3389/feart.2018.00150
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary Palaeoclimate and Contemporary Moisture Source to Extreme NW India: A Review on Present Understanding and Future Perspectives

Abstract: The trans-Himalayan region of NW India including the western part of Tibet, Karakoram, and Hindukush range host thousands of glaciers ensuring perennial freshwater supply to the Indian subcontinent and supports a large fraction of the global population. The peculiar physiography not only limits the entry of water enriched Indian Summer Monsoon winds to this region but also give passage to dry winds of barren desert of the Taklamakan, the Aksai Chin, and western Tibet, to qualify it as a cold desert. The Himala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The semi-arid to arid high altitude terrain of the western Himalayas is referred to "cold desert" due to the scanty rainfall which is attributed to a steady decline in ISM rainfall from east to west/northwest. This decline in the precipitation is ascribed to the Higher Himalayan ranges which act as a barrier and prevent the propagation of moisture laden ISM winds further northward [24][25][26] . Owing to the low precipitation and hence the low erosional rates, the landforms created by past glacier advances (moraines) are better preserved in this region (Figure 3).…”
Section: Study Areamentioning
confidence: 99%
“…The semi-arid to arid high altitude terrain of the western Himalayas is referred to "cold desert" due to the scanty rainfall which is attributed to a steady decline in ISM rainfall from east to west/northwest. This decline in the precipitation is ascribed to the Higher Himalayan ranges which act as a barrier and prevent the propagation of moisture laden ISM winds further northward [24][25][26] . Owing to the low precipitation and hence the low erosional rates, the landforms created by past glacier advances (moraines) are better preserved in this region (Figure 3).…”
Section: Study Areamentioning
confidence: 99%
“…However, the amplitude of such climatic variations during the Holocene is relatively small because the boundary condition of climate system did not change much (Petit et al, 1999). Previous research from the Indian subcontinent revealed a strengthening of the monsoon during the early Holocene Period, but the pattern of mid-to late Holocene monsoon variability is still unclear and often suffers from age uncertainties (Prasad et al, 2014;Mishra et al, 2015;Sharma & Phartiyal, 2018;Banerji et al, 2020;Phartiyal et al, 2021a).…”
Section: Introductionmentioning
confidence: 98%
“…Due to its location in the rain shadow zone of the Indian summer monsoon (ISM), the region receives little precipitation and has abnormally low temperatures with a wide diurnal temperature range and a short growing season (Blöthe et al, 2014;Schmidt and Nüsser, 2017). The scant vegetation in this area is due to the prevailing harsh weather conditions (Ali et al, 2018;Chaddha et al, 2021a;Sharma and Phartiyal, 2018). Ladakh has a diverse range of accessible, diverse, clean, and harsh habitats at extremely high altitudes, including high passes that are distinct due to their altitude and, rocks exposed to 10X more UV-A doses than at sea level (Dvorkin and Steinberger, 1999).…”
Section: Introductionmentioning
confidence: 99%